Structural and electrochemical investigations on the LiNi0.5-xMn1.5-yMx+yO4 (M = Cr, Al, Zr) compound for 5 V cathode material - Oh, Si Hyoung; Chung, Kyung Yoon; Jeon, Sang Hoon; Kim, Chang Sam; Cho, Won Il; Cho, Byung Won (ELSEVIER SCIENCE SA, 2009)
The bare and the metal-doped LiNi0.5Mn1.5O4 high-voltage spinels were prepared under various synthetic conditions and the relationship between their structural and electrochemical properties was investigated. The compound LiNi0.5Mn1.5O4, annealed at 650 degrees C after 800-900 degrees C calcination exhibited very few Mn3+ cations with no sign of impurity phase, and its crystallographic feature showed the ordered spinel, electrochemical property of which was poor possibly due to its intrinsic low electrical conductivity. The compound LiNi0.5Mn1.5O4, quenched quickly from its calcination temperature contained Mn3+ to-ether with NiO-like impurity phase and exhibited non-negligible 4 V plateau in the electrochemical test. The crystal structure of LiNi0.5Mn1.5O4 calcined at low temperature was observed to be normal spinel, the same with the quenched, and the cyclic performance of this compound was much better than the annealed possibly due to its higher electrical conductivity. Raman spectra for Al-and Zr-doped materials indicated that the structure of these materials was ordered spinel, whereas that of Cr-doped material normal spinel. We believe that the excellent electrochemical property of Cr-doped material results from the higher electrical conductivity of this material let alone better chemical and structural stability with less Jahn-Teller distortion for the Cr-doped spinel. (C) 2008 Elsevier B.V. All fights reserved.
Keywords: LITHIUM RECHARGEABLE BATTERIES; LATTICE-VIBRATIONS; VOLTAGE; LINI0.5MN1.5O4; PERFORMANCE; LINIXMN2-XO4; SPINELS; METAL; FE; NI